Spaces of hope: third space identity in selected Muslim chick lit - Siti Hawa Muhamad; Raihanah M.M; Ruzy Suliza Hashim (Penerbit Universiti Kebangsaan Malaysia, 2023)
Minority Muslim women living in Western societies have been continuously marginalised in several contexts. One example is their freedom to visibly project their identity as Muslims and practice Islam as their way of life without being misrepresented or misunderstood. Another is the discriminating cultural practices towards them within the community that they belong to. Using two Muslim chick lit novels as case studies and the theme of ‘spaces of hope’ as explored by Phillips et al., this paper sets out to address the abovementioned issues. The methodology adapts and appropriates the third space theory as a lens to examine public and private experiences of the Muslim female characters in the selected Muslim chick lit. The finding indicates that Muslim chick lit creates female characters who carved out physical space to foreground the negotiation of culture and identity within the Western context. In addition, the finding also shows that the hijab functions as a material space allowing the Muslim female characters to move in and out of the public and personal spheres. Finally, the narratives also present a digital space from which the Muslim female characters can create a site of contestation between culture and identity. This digital space also contests the misrepresentations of and negative assumptions about female Muslim characters. As illustrated in the selected chick lit, spaces of hope are evident in three permutations – physical, material and digital. In conclusion, through this research into selected Muslim chick lit, the theme of spaces of hope is seen as a negotiation area of meaning and representation. It empowers the Muslim storytellers to open up spaces for contemplation and reinterpretation of their identity as Muslim women writers. In the process, it establishes the voices and presence of minority Muslim women within Western popular fiction genre. Keywords: minority identity; Muslim chick lit; Muslim women; spaces of hope; third space